PENGARUH PENGETAHUAN DAN SIKAP SUAMI TERHADAP PERILAKU IBU DALAM PEMBERIAN ASI EKSKLUSIF DI DESA NEGERI SAKTI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Adelia Meutia Putri; Dian Isti Angraini; Sofyan Musyabiq Wijaya (CV. Jasa Sukses Abadi, 2021)
Breast milk is infant food that God made that can not be replaced with any food. Giving breast milk can increase emotional relationship between baby with their mother. The husband who is an integral part of the family and has the role of head of the family, is very necessary for his support so that exclusive breastfeeding is achieved. Some research shows that implementation on giving exclusive breastfeeding will increase if there is a family support. This research purpose is to knowing the effect of husband’s knowledge and attitude towards mother’s behavior on giving exclusive breastfeeding in Negeri Sakti Village, Pesawaran Regency. This research done with analytical observation with case control method. Data source is using secunder data from health centre’s noting and interview with a questionnaire of 60 respondents. The results shows a meaningful relation between husband’s knowledge towards mother’s behavior on giving exclusive breastfeeding in Negeri Sakti Village, Pesawaran Regency (p=0,00) with odds ratio 25,000. And there is a meaningful relation between husband’s attitude towards mother’s behavior on giving exclusive breastfeeding in Negeri Sakti Village, Pesawaran Regency (p=0,007) with odds ratio 4,571).